Transcriptional and translational dynamics underlying heat shock response in the thermophilic crenarchaeon Sulfolobus acidocaldarius - Baes, Rani; Grünberger, Felix; Pyr dit Ruys, Sébastien; Couturier, Mohea; De Keulenaer, Sarah; Skevin, Sonja; Van Nieuwerburgh, Filip; Vertommen, Didier; Grohmann, Dina; Ferreira-Cerca, Sébastien; Peeters, Eveline (mBio, 2023)
High-temperature stress is critical for all organisms and induces a profound cellular response. For Crenarchaeota, little information is available on how heat shock affects cellular processes and on how this response is regulated. We set out to study heat shock response in the thermoacidophilic model crenarchaeon Sulfolobus acidocaldarius, which thrives in volcanic hot springs and has an optimal growth temperature of 75°C. Pulse-labeling experiments demonstrated that a temperature shift to 86°C induces a drastic reduction of the transcriptional and translational activity, but that RNA and protein neosynthesis still occurs. By combining RNA sequencing and mass spectrometry, an integrated mapping of the transcriptome and proteome was performed. This revealed that heat shock causes an immediate change in the gene expression profile, with RNA levels of half of the genes being affected, followed by a more subtle reprogramming of the protein landscape. Functional enrichment analysis indicated that nearly all cellular processes are affected by heat shock. A limited correlation was observed in the differential expression on the RNA and protein level, suggesting a prevalence of post-transcriptional and post-translational regulation. Furthermore, promoter sequence analysis of heat shock regulon genes demonstrated the conservation of strong transcription initiation elements for highly induced genes, but an absence of a conserved protein-binding motif. It is, therefore, hypothesized that histone-lacking archaea such as Sulfolobales use an evolutionarily ancient regulatory mechanism that relies on temperature-responsive changes in DNA organization and compaction induced by the action of nucleoid-associated proteins, as well as on enhanced recruitment of initiation factors. Heat shock response is the ability to respond adequately to sudden temperature increases that could be harmful for cellular survival and fitness. It is crucial for microorganisms living in volcanic hot springs that are characterized by high temperatures and large temperature fluctuations. In this study, we investigated how S. acidocaldarius , which grows optimally at 75°C, responds to heat shock by altering its gene expression and protein production processes. We shed light on which cellular processes are affected by heat shock and propose a hypothesis on underlying regulatory mechanisms. This work is not only relevant for the organism’s lifestyle, but also with regard to its evolutionary status. Indeed, S. acidocaldarius belongs to the archaea, an ancient group of microbes that is more closely related to eukaryotes than to bacteria. Our study thus also contributes to a better understanding of the early evolution of heat shock response.